KARAKTERISASI MI INSTAN YANG DIBUAT DARI TERIGU DENGAN SUBSTITUSI TEPUNG JAGUNG VARIETAS BISI-2 - RENNI NURPITA SARI; USMAN PATO; SHANTI FITRIANI (Universitas Riau, 2018)
This research was aimed to know the effect of substitution of corn flour made from Bisi-2 variety on the qualityand characteristics of instant noodles. This study used Completely Randomized Design (RAL) experimentwith 5 treatments and 3 replications. The treatments in this research included TJ1 (wheat 90: corn flour 10),TJ2 (wheat 80: corn flour 20), TJ2 (wheat 70: corn flour 30), TJ4 (wheat 60: corn flour 40) and TJ5 (wheat50: corn flour 50). The data obtained were tested statistically using the ANOVA and followed by Duncan’sNew Multiple Range Test (DNMRT) test at 5% level. Instant noodles made from wheat flour and corn floursignificantly affected moisture, ash and protein contents, intactness, rehydration time, acid value, descriptiveand hedonic sensory as well as overall assessment. The best treatment was TJ3 (wheat and corn flour 70:30)with moisture content after drying 10,02% , moisture content after frying 7,15%, ash 0,50%, protein 9,23%,and acid value 1,15%. Descriptive sensory assessment resulted in light yellow corn noodles, slightly cornflavour, textured hard and corn taste. The hedonic sensory assessment of the color, aroma, elasticity, andtaste attributes as well as the overall assessment was favored by the panelist.